An annotated checklist of bryophytes of the Nordic countries - Hassel, Kristian; Goldberg, Irina; Huttunen, Sanna; Bjarnason, Ágúst H.; Blom, Hans H.; Hallingbäck, Tomas; Hedenäs, Lars; Høitomt, Torbjørn; Pihlaja, Kati; Prestø, Tommy; Syrjänen, Kimmo; Söderström, Lars; et al. (Dutch Bryological and Lichenological Society and Nordic Bryological Society, 2026)
We present an updated checklist for all bryophyte species known to occur in the Nordic countries and list occurrences for each taxon from Iceland, the Faroe Islands, Denmark, Svalbard, Jan Mayen, Norway (mainland), Sweden and Finland. Altogether 1276 bryophyte species are included for the region. The checklist includes vernacular names in Icelandic, Danish, Norwegian, Swedish and Finnish. The following new nomenclatural combinations are proposed: Scapania scandica var. parvifolia comb. nov., Andreaea alpina var. hartmanii comb. nov., Didymodon islandicus comb. nov., Ephemerum serratum var. stoloniferum comb. nov., Hygroamblystegium varium var. fluviatile comb. nov., Hygroamblystegium varium var. tenax comb. nov., Ptychostomum arcticum var. purpurascens comb. nov., Ptychostomum intermedium var. nitidulum comb. nov. and Ptychostomum warneum var. mamillatum comb. nov.